The P522R protective variant of PLCG2 promotes the expression of antigen presentation genes by human microglia in an Alzheimer's disease mouse model. Issue 10 (9th February 2022) - Claes, Christel; England, Whitney E.; Danhash, Emma P.; Kiani Shabestari, Sepideh; Jairaman, Amit; Chadarevian, Jean Paul; Hasselmann, Jonathan; Tsai, Andy P.; Coburn, Morgan A.; Sanchez, Jessica; Lim, Tau En; Hidalgo, Jorge L. S.; et al.
Abstract: The P522R variant of PLCG2, expressed by microglia, is associated with reduced risk of Alzheimer's disease (AD). Yet, the impact of this protective mutation on microglial responses to AD pathology remains unknown. Chimeric AD and wild‐type mice were generated by transplanting PLCG2‐P522R or isogenic wild‐type human induced pluripotent stem cell microglia. At 7 months of age, single‐cell and bulk RNA sequencing, and histological analyses were performed. The PLCG2‐P522R variant induced a significant increase in microglial human leukocyte antigen (HLA) expression and the induction of antigen presentation, chemokine signaling, and T cell proliferation pathways. Examination of immune‐intact AD mice further demonstrated that the PLCG2‐P522R variant promotes the recruitment of CD8 + T cells to the brain. These data provide the first evidence that the PLCG2‐P522R variant increases the capacity of microglia to recruit T cells and present antigens, promoting a microglial transcriptional state that has recently been shown to be reduced in AD patient brains.